2022
DOI: 10.1186/s42523-022-00186-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes of the Sydney Rock Oyster are acquired through both vertical and horizontal transmission

Abstract: Background The term holobiont is widely accepted to describe animal hosts and their associated microorganisms. The genomes of all that the holobiont encompasses, are termed the hologenome and it has been proposed as a unit of selection in evolution. To demonstrate that natural selection acts on the hologenome, a significant portion of the associated microbial genomes should be transferred between generations. Using the Sydney Rock Oyster (Saccostrea glomerata) as a model, we tested if the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…temperature, pH, salinity, pCO 2 ) [34][35][36][37][38]. In addition to important fluctuations in response to environmental changes, physiological status and developmental stages, the oyster microbiota shows important inter-individual variability, both at the level of the whole animal and at the level of individual tissues throughout all life stages [8, [11][12][13]39]. This heterogeneity has made it difficult to identify the core bacterial microbiota in oysters, if one exists.…”
Section: Homeostasis: a Diversified And Fluctuating Microbiota Cohabi...mentioning
confidence: 99%
See 3 more Smart Citations
“…temperature, pH, salinity, pCO 2 ) [34][35][36][37][38]. In addition to important fluctuations in response to environmental changes, physiological status and developmental stages, the oyster microbiota shows important inter-individual variability, both at the level of the whole animal and at the level of individual tissues throughout all life stages [8, [11][12][13]39]. This heterogeneity has made it difficult to identify the core bacterial microbiota in oysters, if one exists.…”
Section: Homeostasis: a Diversified And Fluctuating Microbiota Cohabi...mentioning
confidence: 99%
“…As filter feeders, oysters evolve in a rich microbial environment, under constant interaction with pathogenic, commensal and beneficial microorganisms. In a recent study, Unzueta-Martínez et al showed that not all members of the oyster-associated microbiota are governed by the same ecological dynamics and that both horizontal and vertical transmission routes are possible [ 13 ]. Particularly the authors identified some members of the bacterial communities that establish at early developmental stages (from gametes to spats) and persist across multiple life stages [ 13 ].…”
Section: The Microbiota Shapes the Oyster Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Other mechanisms include early inoculation during seed formation, egg laying, or passage through the birth canal ( 13 15 ). The mechanisms for vertical transmission have been extensively investigated in invertebrates, such as insects, nematodes, sponges, clams, and oysters ( 16 19 ). However, research on vertical transmission in vertebrates, especially other than Mammalia, has been limited.…”
Section: Introductionmentioning
confidence: 99%